Uji Aktivitas Antibakteri Ekstrak Air Bunga Kecombrang terhadap Bakteri E. coli dan S. aureus sebagai Bahan Pangan Fungsional - Adeng Hudaya; Nani Radiastuti; Dede Sukandar; Ira Djajanegara (Al-Kauniyah: Jurnal Biologi, 2014)
The testing has been conducted research on the antibacterial activity of aqueous extracts of flowers kecombrang against E. coli and S. Aureus. This study was aims to provided scientific evidence of excellence kecombrang plants as functional food ingredients. Antibacterial activity assays performed using dispersive method. From the results of antibacterial testing kecombrang flower water extract against E. coli concentration of 20% = 0 mm, 40% = 0 mm, 60% = 4.8 mm, 80% = 5.2 mm, 100% = 7.3 mm and the test bacteria S. aureus concentration of 20% = 8.67 mm, 40% = 9.11 mm, 60% = 12:33 mm, 80% = 12:44 mm, 100% = 13.89 mm.